Electrophysiological Correlates of Familiarity and Recollection in Associative Recognition: Contributions of Perceptual and Conceptual Processing to Unitization - Li, Bingcan; Mao, Xinrui; Wang, Yujuan; Guo, Chunyan (Frontiers in Human Neuroscience, 2017)
It is generally accepted that associative recognition memory is supported by recollection. In addition, recent research indicates that familiarity can support associative memory, especially when two items are unitized into a single item. Both perceptual and conceptual manipulations can be used to unitize items, but few studies have compared these two methods of unitization directly. In the present study, we investigated the effects of familiarity and recollection on successful retrieval of items that were unitized perceptually or conceptually. Participants were instructed to remember either a Chinese two-character compound or unrelated word-pairs, which were presented simultaneously or sequentially. Participants were then asked to recognize whether word-pairs were intact or rearranged. Event-related potential (ERP) recordings were performed during the recognition phase of the study. Two-character compounds were better discriminated than unrelated word-pairs and simultaneous presentation was found to elicit better discrimination than sequential presentation for unrelated word-pairs only. ERP recordings indicated that the early intact/rearranged effects (FN400), typically associated with familiarity, were elicited in compound word-pairs with both simultaneous and sequential presentation, and in simultaneously presented unrelated word-pairs, but not in sequentially presented unrelated word-pairs. In contrast, the late positive complex (LPC) effects associated with recollection were elicited in all four conditions. Together, these results indicate that while the engagement of familiarity in associative recognition is affected by both perceptual and conceptual unitization, conceptual unitization promotes a higher level of unitization. In addition, the engagement of recollection was not affected by unitized manipulations. It should be noted, however, that due to experimental design, the effects presented here may be due to semantic rather than episodic memory and future studies should take this into consideration when manipulating rearranged pairs.